Legal, regulatory and governance issues in Islamic finance - Wilson, Rodney (Edinburgh : Edinburgh University Press, 2012)
"From Iran, where all banking is Shari'ah compliant, to Malaysia and the gulf, where Islamic financial institutions compete with conventional banks, Rodney Wilson examines how Islamic financial institutions are licensed and governed by common and civil law. Covering Islamic banks, takaful operators, fund management and Shari'ah-compliant securities, it examines how their assets and liabilities differ from their conventional counterparts and what the implications are for risk management."--Publisher.
Introduction -- Common law, civil law and Shari'ah -- Terms and conditions governing Islamic bank deposits -- Contracts for Islamic financing -- Laws providing for comprehensive Islamic banking systems -- Laws providing for parallel Islamic banking systems -- Regulation of Islamic banks -- Laws and reglations for takaful operators and participants -- Sukuk structures and their contractual implications -- Shari'ah monitoring and regulatory supervision of Islamic funds -- Corporate governance in Islamic financial institutions -- Plurality, diversity and post-Arab Spring Islamic finance possibilities.
Includes bibliographical references and index.
Keywords: Banking law (Islamic law); Finance (Islamic law)